Nasal carriage of meticillin-resistant Staphylococcus aureus among children living with HIV attending Infectious Diseases Clinics in Kano, Nigeria - Aisha Habib Sadauki; Abdulhakeem Abayomi Olorukooba; Muhammad Shakir Balogun; Mahmood Muazu Dalhat; Hyelshilni Waziri; Mukhtar Muhammad Abdulaziz; Chukwuma David Umeokonkwo; Fatimah Hassan-Hanga; Kabir Sabitu (Elsevier, 2022)
Summary: Background: Children living with HIV (CLWH) are at risk of colonisation and infection with meticillin-resistant Staphylococcus aureus (MRSA). All S. aureus isolates from CLWH with bloodstream infections in Kano were MRSA. Aim: To estimate the prevalence of nasal colonisation with S. aureus and MRSA in CLWH in Kano State and to determine associated risk factors. Methods: A cross-sectional study was performed in the infectious diseases clinics of two public hospitals in Kano involving 214 CLWH/caregiver pairs. Children were selected from clinic registers by simple random sampling and an interviewer-administered questionnaire used to elicit factors associated with MRSA carriage from the caregivers. Clinical records were reviewed for patients' medical histories. Standard laboratory techniques were used to isolate S. aureus from nasal swabs collected from CLWH. MRSA was detected using the cefoxitin disc diffusion method and PCR for mecA gene detection. We measured the prevalence of S. aureus and MRSA carriage in the CLWH and calculated adjusted odds ratios (AOR) for factors associated with MRSA. Results: Nasal S. aureus carriage in CLWH was 18.7% (40/214). Cefoxitin disc diffusion identified 6/214 (2.8%) of CLWH were MRSA carriers, while PCR identified that 9/214 (4.2%) of CLWH were MRSA carriers. Recent hospitalisation (AOR: 61.04; 95% CI: 9.01-413.38) and recent antibiotic therapy (AOR: 7.52; 95% CI: 1.07-52.95) were independent risk factors for MRSA colonisation. Conclusions: The rate of MRSA nasal colonisation among CLWH in Kano was similar to that reported in other studies in Africa. Infection prevention and control measures including MRSA screening and decolonisation, as well as education for CLWH and their carers should be introduced to reduce MRSA spread.